Capillary Pressure Measurements for CO2, Brine and Berea Sandstone at Reservoir Conditions - Sarmadivaleh, Mohammad; Iglauer, Stefan (EAGE, 2014)
Technically, we conducted a capillary pressure experiment using the methodology suggested by Pini et al. (2012): we injected scCO2 into a sandstone plug which was fully saturated with CO2-saturated brine. This method assumes that the applied viscous pressures are equal to the capillary pressures. Initially a low CO2 injection rate was applied and once steady-state was reached the injection pressure and the brine saturation in the plug were measured. In our case, the brine saturation in the plug was measured by volume balance, the volume of produced brine was measured in a separate ISCO pump. This process was then repeated at incrementally increasing CO2 flow rates and the capillary pressures at different water saturations were measured (again at steady-state conditions).